2019
DOI: 10.1051/0004-6361/201833973
|View full text |Cite
|
Sign up to set email alerts
|

LoTSS DR1: Double-double radio galaxies in the HETDEX field

Abstract: Context. Double-double radio galaxies (DDRGs) represent a short but unique phase in the life-cycle of some of the most powerful radio-loud active galactic nuclei (RLAGN). These galaxies display large-scale remnant radio plasma in the intergalactic medium left behind by a past episode of active galactic nuclei (AGN) activity, and meanwhile, the radio jets have restarted in a new episode. The knowledge of what causes the jets to switch off and restart is crucial to our understanding of galaxy evolution, while it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 70 publications
3
75
0
Order By: Relevance
“…This possibility has previously been discussed from an empirical stand point (e.g. Harwood et al 2017Harwood et al , 2019Mahatma et al 2019) and is also supported through modelling considerations and numerical simulations (Rudnick 2002;Turner et al 2017), which show that the mixing of different aged electrons strongly affects the spectrum at each point of the radio source leading to poor spectral age estimates. This mixing may have an observational origin, when the resolution of the observation is not high enough to distinguish different particle populations or in case of projection effects (see Harwood et al 2019), and also an intrinsic origin, when there is an actual mixing of particles that are accelerated by different events (i.e.…”
Section: Spectral Ages and Modelsmentioning
confidence: 64%
“…This possibility has previously been discussed from an empirical stand point (e.g. Harwood et al 2017Harwood et al , 2019Mahatma et al 2019) and is also supported through modelling considerations and numerical simulations (Rudnick 2002;Turner et al 2017), which show that the mixing of different aged electrons strongly affects the spectrum at each point of the radio source leading to poor spectral age estimates. This mixing may have an observational origin, when the resolution of the observation is not high enough to distinguish different particle populations or in case of projection effects (see Harwood et al 2019), and also an intrinsic origin, when there is an actual mixing of particles that are accelerated by different events (i.e.…”
Section: Spectral Ages and Modelsmentioning
confidence: 64%
“…It will be possible to adapt LoMorph for use with data from other instruments, but it is important to emphasise that the same sources can present very different appearances depending on the frequency, sensitivity and angular scales to which a survey is sensitive. For example, FIRST data generally only show the inner, newer structures of most double-double sources identified in LoTSS (Mahatma et al 2019;Williams et al 2019), and due to the higher frequency and comparatively poorer sensitivity of FIRST to extended structure, sometimes isolated components belonging to the same source may not be correctly identified as such. It is also crucial to note that deep surveys such as LoTSS contain a large number of ordinary galaxies with star-formation associated radio emission, which we have been able to pre-filter by using the sample selection of Hardcastle (2018a).…”
Section: Labelmentioning
confidence: 99%
“…However, sensitive low frequency observations are at the same time revealing a more complex extended source population, including candidate hybrid radio galaxies, restarting and remnant radio galaxies (e.g. Kapińska et al 2017;Brienza et al 2016Brienza et al , 2017Mahatma et al 2018Mahatma et al , 2019. Simple classification schemes may therefore risk obscuring important physical distinctions.…”
Section: Introductionmentioning
confidence: 99%
“…Sabater et al (2019) found that up to 100 per cent of all large galaxies host an active nucleus, noting that their accretion rate is modulated such that half the energy output is released in outbursts of increased activity lasting less than two percent of the time. Studies of individual objects and large sky surveys have also found populations of remnant (Brienza et al 2017;Mahatma et al 2018) and restarted (Mahatma et al 2019) radio galaxies, setting a lower bound for the dutycycle. Turner (2018) used a radio source dynamical model to provide an upper limit on the duty cycle of δ < 0.15 in the remnant B2 0924+30.…”
Section: Introductionmentioning
confidence: 99%